The prevalence of physical activity among the young population of UAE - Yammine, Kaissar (2017)
Aims: Lack of physical activities is a key disease factor and constitutes a serious public health issue in the Middle East region. Reports from this geographical area converge in concluding that the resident populations do not get enough exercise to keep themselves healthy. The objective of this systematic review is to obtain accurate data on the prevalence of physical activity (PA) and levels of PA among the young residents of the United Arab Emirates (UAE). Methods: Five prospective studies met the inclusion criteria with 12,988 subjects (including 12,782 adolescents). Results: Meta-analytical results showed that (1) almost a quarter of the young population have a total sedentary lifestyle with no PA, (2) less than half have been mildly involved in physical activities, (3) around a fifth practised a moderate level of PA, and (4) a quarter were involved in a vigorous PA. Additionally, mild PA was more common in female adolescents, whereas moderate and high PA were significantly higher in male adolescents. Conclusion: Such alarming rates of exercise involvement among the young UAE residents should stimulate policymakers and college/university administrations to plan and promote PA in order to reduce future levels of chronic diseases. Keywords